Abdominal wall metastasis of carcinoma breast : a case report - Bhattacharjee, Abhishak; Rassell, Md; Hasan, Md Nazmul; Debnath, Bidyut Chandra (Bangladesh Medical Journal, 2016)
Abdominal wall metastasis from breast carcinoma is an uncommon occurrence compared to local invasion into muscle from direct tumor spread. A 30 years old lady was referred to our hospital from a medical college hospital for adjuvant treatment after being done the left sided modified radical mastectomy. Pathological examination revealed poorly differentiated infiltrative duct cell carcinoma, metastatic deposits in axillary lymph node with histological grade 3. She underwent adjuvant chemotherapy and radiotherapy with regular schedule and follow up. Her adjuvant treatment and follow up period were uneventful upto 13 months. Thereafter she reported a painless lump in the right upper abdomen which was rapidly growing in size. Cytopathology report confirmed that the cells of the parietal lump were compatible with metastatic duct cell carcinoma. So, though the primary pathology was in the left side but the parietal lump was found in the right side. Skeletal muscle metastasis is uncommon and pain is the commonest symptom. But here the lump is painless and this is another rare presentation. Treatment principle is only palliation. Bangladesh Med J. 2015 Sep; 44 (3): 172-174